2019
DOI: 10.1177/0268355519889873
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral deep vein thrombosis after stenting across the iliocaval confluence in chronic venous disease – A systematic review

Abstract: Objective Stenting of the iliac veins is increasingly considered in the presence of symptomatic obstructive chronic lesions in the iliac vein segment. However, it is often necessary to extend the stented zone into the inferior vena cava, increasing the risk of contralateral iliac vein thrombosis. This study aims to review the current literature concerning the incidence of contralateral deep vein thrombosis after stenting across the iliocaval confluence. Methods A systematic review from potentially relevant pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…It usually results from stenting into the IVC, which is often unavoidable, thereby jailing the contralateral iliac vein. 391 5.3.6. Multidisciplinary team.…”
Section: Safety Issuesmentioning
confidence: 99%
“…It usually results from stenting into the IVC, which is often unavoidable, thereby jailing the contralateral iliac vein. 391 5.3.6. Multidisciplinary team.…”
Section: Safety Issuesmentioning
confidence: 99%
“…34 In the context of DVT, catheter-directed thrombolysis is commonly used with insufficient consensus on ideal patient selection and considerable variation in protocols and outcome assessments. Duarte-Gamas et al 35 conducted a systematic review and meta-analysis to address this variability, which underscored the need for standardized reporting in catheter-directed thrombolysis protocols and patient-centered outcomes. 36…”
Section: Working Against the Clotmentioning
confidence: 99%
“…[15][16][17] Information on the use of venous stenting and its complications in patients with acute or chronic DVT is largely based on observational studies, primarily consisting of case series and retrospective studies, as shown in recent systematic reviews. [18][19][20][21][22][23][24][25] In this context, a panel of experts from the Spanish Society of Internal Medicine, Spanish Society of Vascular and Interventional Radiology, and Spanish Society of Angiology and Vascular Surgery was assembled by the collaborating societies. We aimed to evaluate the available evidence and formulate specific recommendations regarding the indications, placement, follow-up, and prevention of complications associated with the use of venous stents for the management of DVTof the lower extremity.…”
mentioning
confidence: 99%